Calibration of the Little Beaver Creek Watershed - Murray, David Lindley (Colorado State University. Libraries, 2021)
March 1968. Includes bibliographical references (pages 74-77). Covers not scanned. Print version deaccessioned 2021. Proposed logging operations on Little Beaver Creek provide an opportunity to add to the knowledge of timber-cutting effects on streamflow. This study was concerned with calibrating Little Beaver Creek In order that parameters of water yield, high and low flow, and streamflow timing could be evaluated after treatment as If treatment had not occurred. Precision of prediction relationships was assessed in terms of changes in the parameters which would be statistically detectable when six years of after-treatment data are available. A change equivalent to 20 percent of the mean value of parameters in the period 1961 to 1966, was considered to be the smallest acceptable effect of treatment. Double-mass curves of water yield from the study area against either precipitation data or concurrent water yield data from a nearby watershed showed some consistency, but precise linear relationships could not be defined. Monthly, seasonal, and annual water yield volumes from Little Beaver Creek were correlated by simple, least squares regression with each of the following: concurrent precipitation data; water yield data from two adjacent watersheds; and snow water equivalent records from a snow course within the watershed. The only equation meeting the precision criteria had a combination of snow water equivalent measurements as the control variable. Other equations were generally less precise, though some which Involved monthly yields had high correlation coefficients. Similar analyses for peak flows, half-flow Intervals, low flow Intervals, and discharge levels corresponding to ten percentages of time on the annual flow-duration curve, were made using corresponding data from the adjacent watersheds as control variables. The arbitrary level of detectable change could not be met with consistency for any of these parameters. It was concluded that available precipitation records do not provide an accurate ...